A RESCUE OF JOURNALISM: from rise to immersion - Oliveira, Sheila Borges de (2017)
This article aims to contribute to the debate on the future of journalism in times of technological convergence: how to reconfigure to continue to be recognized as the actual construction field, giving meaning to the tangle of information circulating in the virtual world? This paper considers that one of the answers may be in the use of virtual reality, which is no longer restricted to the world of video games. The reports produced with virtual reality lead the audience to have immersive experiences. With virtual reality, journalism invites citizens to a new experience: being in the event site. Finally, the research finds that the immersive culture can bring journalism to a review of its histórica l phases.